Standing low‐field MRI of the equine proximal metacarpal/metatarsal region is considered useful for diagnosing primary bone pathology and makes a positive contribution to case management: A prospective survey study. Issue 2 (4th December 2019) - Labens, Raphael; Schramme, Michael C.; Murray, Rachel C.; Bolas, Nick
Abstract: High‐field MRI of the proximal metacarpal/metatarsal region has been associated with great diagnostic potential and clinical reports of standing low‐field MRI of the forelimb suggest the same. To better understand diagnostic outcomes with standing low‐field MRI of the proximal suspensory region, a prospective survey study was conducted and users of a widely available system questioned on their experience, operating procedures, and interpretation of standing low‐field MRI findings. Response data included scores on a modified Likert scale from which weighted ratings were calculated for statistical analyses. Depending on the question, responses were obtained from 17 to 29 of the 38 invited facilities. Users indicated that standing low‐field MRI was most frequently performed in the face of equivocal diagnostic findings; compared to Sports horses, general purpose riding horses were thought less likely to have detectable abnormalities and standing low‐field MRI was rated most useful for the detection of primary bone pathology in the proximal metacarpal region. Standing low‐field MRI signal change involving both the suspensory ligament and adjacent bone concurrently was rated most relevant and abnormalities solely affecting the muscle/adipose tissue bundles least relevant for diagnosing suspensory ligament injury. Transverse scans and in decreasing order T1‐weighted gradient echo, short‐tau inversion recovery FSE, T2*‐weighted gradient echo, and T2‐weighted FSE sequences were most frequently acquired and judged most useful by the majority of users experienced in imaging of the target area. This survey supports the relevant impact of standing low‐field MRI on clinical case management, particularly in the context of imaging the proximal metacarpal region.